Attracting Foreign Investment in Cyclic Imbalances of the Economy - Trusova, Natalia; Трусова, Наталя Вікторівна; Kotvytska, Nataliia; Котвицька, Наталія Миколаївна; Pikhniak, Tetiana; Пихняк, Тетяна Андріївна; Pavlova, Maryna; Павлова, Марина Борисівна; Plotnichenko, Svitlana; Плотніченко, Світлана Романівна; Sakun, Alina; Сакун, Аліна Жоржівна (My University, 2022)
EN: Foreign investment is an important economic resource for many countries including Ukraine. The relevance of this study lies in the need to solve problems of attracting foreign investment. The purpose of this study was to consider the conditions for attracting foreign investment in the cyclic imbalances of the world economy. Using the method of correlation-regression analysis, the impact of indicators of financial imbalances was found both in general and by individual sub-indices. The study found the financial imbalances (fiscal, monetary, exchange rate, debt, trade, households, investment, and savings), both present and potential, in the face of the threat of financial and economic crisis. The procedure for assessing financial imbalances in economic activity of the world and their regional groups that implement the process of investment-oriented development was defined. To assess their impact on the volume of foreign direct investment, a comprehensive method of calculating sub-indicators of financial imbalances was proposed, which on the set of certain parameters forms an integrated index of financial imbalances. Methodological approaches to determining the restrictive procedures for the accumulation of financial imbalances associated with the transition of the financial system to a state of financial danger, considering the budget, currency, monetary and debt components were substantiated. The complex method of calculating sub-indicators of financial imbalances in the economy involves the identification of economic risks at the initial stages using the Alert Mechanism on the violation of the balance of the financial and economic systems of the participating countries. Priority areas (real estate and professional services) for attracting foreign investment from around the world were identified. The geostrategic matrix of attraction of foreign investments by the countries of the world was offered. /// UA: Іноземні інвестиції є важливим економічним ресурсом для багатьох країн, у тому числі для України. Актуальність дослідження полягає в необхідності вирішення проблем залучення іноземних інвестицій. Стаття спрямована на розгляд умов залучення іноземних інвестицій в умовах циклічної диспропорції світової економіки. За допомогою методу кореляційно-регресійного аналізу визначено вплив показників фінансових дисбалансів як у цілому, так і за окремими субіндексами. Виявлено наявні та потенційні фінансові дисбаланси (фіскальні, монетарні, курсові, боргові, торгові, домогосподарські, інвестиційні та заощаджувальні) в умовах загрози фінансово-економічної кризи. Визначено порядок оцінки фінансових дисбалансів в економічній діяльності країн світу та їх регіональних угруповань, які реалізують процес інвестиційно-орієнтованого розвитку. Для оцінки їх впливу на обсяг прямих іноземних інвестицій запропоновано комплексну методику розрахунку субіндикаторів фінансових дисбалансів, яка за сукупністю певних параметрів формує інтегральний індекс фінансових дисбалансів. Обґрунтовано методологічні підходи до визначення обмежувальних процедур накопичення фінансових дисбалансів, пов’язаних із переходом фінансової системи у стан фінансової небезпеки, з урахуванням бюджетної, валютної, грошово-кредитної та боргової складових. Комплексна методика розрахунку субіндикаторів фінансових дисбалансів в економіці передбачає ідентифікацію економічних ризиків на ранніх етапах за допомогою механізму оповіщення про порушення збалансованості фінансово-економічних систем країн-учасниць. Визначено пріоритетні напрями (нерухомість і професійні послуги) для залучення іноземних інвестицій з усього світу. Запропоновано геостратегічну матрицю залучення іноземних інвестицій країнами світу.
Залучення іноземних інвестицій в умовах циклічної незбалансованості економіки
Keywords: financial and economic crisis; budget; currency; redistribution; reforms; фінансово-економічна криза; бюджет; валюта; перерозподіл; реформи